An Islamic finance model for the small and medium-sized enterprises in France - Oseni, Umar Aimhanosi; Hassan, M. Kabir; Matri, Dorsaf (King Abdulaziz University Scientific Publishing Center, 2013)
The dominant effect of the global financial shockwaves ravaging the whole of Europe is becoming proverbial in the history of world economic crises. This has been largely due to untoward economic policies that have negatively impacted most economies in Europe. The recent European sovereign debt crisis experienced more in Greece, Italy, Spain and Portugal, and the most  recent  downgrade  of  France’s  credit  rating  by  Standard  and   Poor’s  call  for  a  rethinking  of  the  existing  economic  policies.  The   need to foster innovation in Small and Medium-sized Enterprises (SMEs) and sustainably support the existing ones has remained a major challenge in France. With over 2.5 million SMEs in France, the recent report of the Institut Nationale de la Statistiqueet des Etudes Economiques [INSEE] reveals that one in every two new business fails in the long run. This paper examines the need to find credible alternatives for French SMEs to the collateral-based debt financing. Built on ethical business models, the Islamic SMEs and microfinance models are expected to foster innovation and sustainability to smaller economic players. Although, loans  remain  SMEs’  main  source of financing, banks require more collateral from entrepreneurs, and now provide lower financing compared to the period before the financial crisis. In this context of financial difficulties for SMEs, considering alternative models of financing such as Islamic financial products based on the profit and loss sharing has increased the interest of many European countries. While focusing on the econo-legal issues underlying any of such proposals, the paper considers the feasibility of Islamic venture capital as a credible alternative to  bank’s  loans  for  SMEs within the existing French legal and regulatory framework.